Isolation and characterization of fifteen ecdysone-inducible Drosophila genes reveal unexpected complexities in ecdysone regulation. - Hurban, P.; Thummel, C.S. (Molecular and Cellular Biology, 1993)
Our insights into the regulatory mechanisms by which the steroid hormone ecdysone triggers Drosophila melanogaster metamorphosis have largely depended on puffs in the larval salivary gland polytene chromosomes as a means of identifying genes of interest. Here, we describe an approach that provides access to ecdysone-inducible genes that are expressed in most larval and imaginal tissues, regardless of their ability to form puffs in the polytene chromosomes. Several hundred cDNAs were picked at random from subtracted cDNA libraries and subjected to a rapid and sensitive screen for their ability to detect mRNAs induced by ecdysone in the presence of cycloheximide. Of the 15 genes identified in this manner, 2 correspond to early puffs in the salivary gland polytene chromosomes, at 63F and 75B, confirming that this screen functions at the desired level of sensitivity and is capable of identifying novel primary-response genes. Three of the genes, Eig45-1, Eig58, and Eig87, are expressed coordinately with the salivary gland early genes; one of them, Eig58, maps to the 58BC puff that is active when the 74EF and 75B early puffs are at their maximal size. Another gene identified in this screen, Eig17-1, encodes a novel cytochrome P-450. On the basis of its sequence identity and temporal profile of expression, this gene may play a role in steroid hormone metabolism and thus could provide a mechanism for feedback regulation of ecdysone production. Although all 15 genes have patterns of transcription that are consistent with ecdysone regulation in vivo, 5 genes do not appear to be induced by the late larval ecdysone pulse. This indicates that ecdysone induction in larval organs cultured with cycloheximide is not always indicative of a primary response to the hormone.